Pengembangan Sistem Informasi CSIRT Berbasis Web Menggunakan Framework Laravel dengan Metode Prototyping pada Diskominfo Purwakarta - Muhammad Rifky Akbar; Aidah Nur Fadhilah; Aji Primajaya (Jurnal Informatika Terpadu, 2026)
The increasing threat of cybersecurity attacks on regional government infrastructure requires a structured incident handling mechanism. However, cybersecurity incident handling at the Diskominfo of Purwakarta Regency is still conducted manually, resulting in slow responses and unstructured documentation. Previous studies discuss policies for CSIRT formation and Laravel-based system security, but none have developed a web-based CSIRT information system for the operational needs of incident response teams at the regional government level. This study aims to develop a web-based CSIRT (Computer Security Incident Response Team) information system using the prototyping method at the Diskominfo of Purwakarta Regency. The development process includes the stages of requirements analysis, design, prototyping, customer evaluation, review and refinement, development, testing, and release. Data collection is conducted through observation, interviews, and literature study. Testing uses Black Box Testing across 12 scenarios covering authentication, incident ticket management, incident reporting, security vulnerability notification letters, and report recapitulation, achieving a 100% success rate. It is concluded that this system can improve the effectiveness of cybersecurity incident handling through structured documentation and integrated report management. It is recommended that the system be integrated with the BSSN reporting system and developed as a mobile application.